THE EFFECT OF CAREER EXPECTATION, CAREER GUIDANCE, AND WORK MOTIVATION TOWARD WORK READINESS STUDENT - Gifaninda Sofiani; Abdullah Taman (Universitas Negeri Yogyakarta, 2019)
This research aims to determine: 1) The effect of Career Expectation toward Work Readiness student, 2) The effect of Career toward Work Readiness student, 3) The effect of Work toward Work Readiness student, 4) The effect of Career Expectation, Career Guidance, and Work Motivation simultaneoulsy toward Work Readiness student. This research is an Ex-post facto study with a quantitative approach, conducted at SMK Negeri 1 Bantul with the subject of student of XII Accounting Grader. The data collection technique used was a questionnaire. Before analyzing the data, a prerequisite test for analysis must be carried out, namely normality test, linearity test, and multicollinearity test. The data analysis technique used in this study is simple regression analysis and multiple regression analysis. The results of this study are: 1) There is a positive and significant influence between Career Expectation and Work Readiness with a value of r2x1y 0.153. 2) There is a positive and significant influence between Career Guidance and Work Readiness with a value of r2x2y 0.205. 3) There is a positive and significant influence between Work Motivation and Work Readiness toward Work Readiness student with r2x3y 0.124. 4) There is a positive and significant influence between Career Expectation, Career Guidance, and Work Motivation simultaneoulsy toward Work Readiness student with a value of R2(1,2,3) 0,283. So Career Guidance is a variable with the greatest influence among the three independent variables with r2x2y 0.205 so student can be more active in doing Career Guidance that supports Student toward Work Readiness. Keywords: Work Readiness, Career Expectation, Career Guidance, Work Motivation